Choosing an anchor currency for the Pacific - Stephan Freitag (Verein für Socialpolitik, 2010)
This paper analyses currency options for six Pacific states - Fiji, Papua New Guinea, Samoa, Solomon Islands, Tonga and Vanuatu - that issue their own currencies. Empirical estimates indicate that these states already stabilize their currencies against the US dollar because of their large and increasing trade with emerging Asia which denominates its trade in US dollars. Building on the theory of an optimal peg, we argue that the replacement of present currencies by the US dollar would strengthen these countries' trade. Gravity model estimations indicate that adopting a common external currency would be a major stimulus to Pacific trade. While the Australian dollar has been suggested because of the Pacific's traditional trade relations with Australia this choice would be the result of a reverse causality bias. A binary choice method is applied to trace endogeneity biases in the Pacific sample. The gains for trade from the adoption of an external currency are lower but remain positive.
Keywords: C21; F15; F33; 330; Currency regimes; gravity model; binary choice; Pacific